Implementasi Ekonomi Sirkular dalam Pengelolaan Sampah di Pemerintahan Desa Panggungharjo - pratiwi, Nurna Pratiwi; Hilmiawan, Gigih Aulia (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2024)
Nowadays in Indonesia, environmental issues have become an important factor that requires special attention, considering the less than optimal management of the environment. Several disasters that have occurred recently illustrate this phenomenon, such as flash floods in several areas of Central Java, East Java, and Jakarta; landslides in Sijeruk village, Central Java, and other areas in Java and Sumatra; and forest fires in the Protected Forest of Kalimantan. Currently, the approach of circular economy has become an important strategy for various parties in addressing waste management issues and the impact of increasing greenhouse gas effects. The circular economy is a concept where the resources produced are processed to be continuously utilized, so they do not become waste or are discarded carelessly. This concept has the potential to lead to sustainability while separating economic growth from the negative impacts of resource depletion and environmental pollution. This research uses a qualitative approach and applies phenomenological study using a model based on the concepts of Strauss and Corbin. Breaking down the coding process into three stages: open coding, axial coding, and selective coding. The results of the research on circular economy in waste management at the village government level reveal a meaning that illustrates the reality occurring within the context of village governance. In determining this meaning, the researcher categorized it into one part, namely the implementation of the circular economy in waste management. This category was further described by the researcher in two aspects: efforts to enhance social aspects and efforts to improve economic aspects. The implications of this research indicate that the circular economy-based waste management model in KUPAS Panggungharjo can serve as an example for other villages. Community participation and the role of the village government are very important for the successful implementation of it. In addition, this research emphasizes the need for local policies that support and enhance the capacity of village governments in managing similar initiatives. The novelty of this research analyzes the application of circular economy in waste management at the village level, particularly through the KUPAS Panggungharjo initiative, which can serve as a model for other villages in Indonesia. This study also highlights the important role of village governments in supporting these initiatives, as well as providing a holistic view that encompasses technical, social, and economic aspects. In addition, this research explores the challenges and opportunities in the implementation of a circular economy in villages, providing insights for more effective strategies in the future.